1995
DOI: 10.1002/nur.4770180308
|View full text |Cite
|
Sign up to set email alerts
|

Parental relationships, coping strategies, received support, and well‐being in adolescents of separated or divorced and married parents

Abstract: The purpose of this cross-sectional study was to examine the impact of the perceived quality of the parental relationship and family status on coping strategies, received support, and well-being in adolescents from separated or divorced and married parents. Two hundred forty-four matched adolescents from separated/divorced and married households were drawn from an initial sample of 1,044 students who were tested at five colleges and three high schools of a large metropolitan and rural area. Regression analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
1
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 44 publications
(49 reference statements)
3
18
1
4
Order By: Relevance
“…Research findings on the psychological, emotional, and behavioural effects of divorce on children and adolescents have been mixed (Grossman and Rowat 1995), and research findings demonstrate that there is substantial variation in how children respond to the experience (Greene et al 2006). On a general level, parental separation, divorce, and remarriage have been shown to be associated with diminished well-being in adolescents (Demo and Acock 1996), whereas more complex familial variables such as lack of paternal involvement have been shown to exert a greater negative effect (Flouri and Buchanan 2002;Grossman and Rowat 1995). For example, Grossman and Rowat (1995) found that perceived poor parental relationship, and not family status, was associated with reduced LS among a group of Canadian adolescents.…”
Section: Parental Marital Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Research findings on the psychological, emotional, and behavioural effects of divorce on children and adolescents have been mixed (Grossman and Rowat 1995), and research findings demonstrate that there is substantial variation in how children respond to the experience (Greene et al 2006). On a general level, parental separation, divorce, and remarriage have been shown to be associated with diminished well-being in adolescents (Demo and Acock 1996), whereas more complex familial variables such as lack of paternal involvement have been shown to exert a greater negative effect (Flouri and Buchanan 2002;Grossman and Rowat 1995). For example, Grossman and Rowat (1995) found that perceived poor parental relationship, and not family status, was associated with reduced LS among a group of Canadian adolescents.…”
Section: Parental Marital Statusmentioning
confidence: 99%
“…On a general level, parental separation, divorce, and remarriage have been shown to be associated with diminished well-being in adolescents (Demo and Acock 1996), whereas more complex familial variables such as lack of paternal involvement have been shown to exert a greater negative effect (Flouri and Buchanan 2002;Grossman and Rowat 1995). For example, Grossman and Rowat (1995) found that perceived poor parental relationship, and not family status, was associated with reduced LS among a group of Canadian adolescents. These results are supportive of similar research, such as that conducted by Heaven et al (1996) among Australian adolescents, where perceived family functioning was found to be positively associated with LS, self-esteem, and extraversion, and negatively associated with neuroticism and psychoticism.…”
Section: Parental Marital Statusmentioning
confidence: 99%
“…These variables were controlled because they are likely to be related to life satisfaction [Diener et al, 1999]. Growing up in intact families is related to higher life satisfaction in adolescence [Sastre and Ferriere, 2000], although other studies found no family structure effect [e.g., Grossman and Rowat, 1995], and others have shown that parental marital conflict was a stronger predictor of offspring low feelings of subjective well-being than divorce per se [Gohm et al, 1998]. On the other hand, prospective epidemiological studies of child and adolescence depressive disorders reveal a dramatic increase in the prevalence of major depressive disorders after age 11 years and a similarly dramatic increase in first admission rates after age 15 years [Merikangas and Angst, 1995].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on adolescents and emerging adults has addressed relations between coping strengths and parental divorce (Duran-Aydintug, 1997;Gonzalez et al, 1995;Grossman & Rowat, 1995;). Non-normative changes such as divorce tax individuals' abilities to cope (Martinson & Campo, 1991).…”
mentioning
confidence: 99%